Light pollution may create demographic traps for nocturnal insects - Firebaugh, Ariel; Haynes, Kyle J. (Basic and applied ecology, 2019)
Light pollution impacts both intra- and inter-specific interactions, such as interactions between mates and predator–prey interactions. In mobile organisms attracted to artificial lights, the effect of light pollution on these interactions may be intensified. If organisms are repelled by artificial lights, effects of light pollution on intra- and inter-specific interactions may be diminished as organisms move away. However, organisms repelled by artificial lights would likely lose suitable habitat as light pollution expands. Thus, we investigated how light pollution affects both net attraction or repulsion of organisms and effects on intra- and inter-specific interactions. In manipulative field studies using fireflies, we found that Photuris versicolor and Photinus pyralis fireflies were lured to artificial (LED) light at night and that both species were less likely to engage in courtship dialogues (bioluminescent flashing) in light-polluted field plots. Light pollution also lowered the mating success of P. pyralis. P. versicolor is known to prey upon P. pyralis by mimicking the flash patterns of P. pyralis, but we did not find an effect of light pollution on Photuris–Photinus predator–prey interactions. Our study suggests, that for some nocturnal insects, light-polluted areas may act as demographic traps, i.e., areas where immigration exceeds emigration and inhibition of courtship dialogues and mating reduces reproduction. Examining multiple factors affecting population growth in concert is needed to understand and mitigate impacts of light pollution on wildlife.